2013
DOI: 10.1007/s00134-013-2868-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia after out-of-hospital cardiac arrest in Finnish intensive care units: the FINNRESUSCI study

Abstract: One-year unfavourable neurological outcome of patients with shockable rhythms after TH was lower than in previous randomized controlled trials. However, our results do not support use of TH in patients with non-shockable rhythms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
90
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 36 publications
3
90
2
5
Order By: Relevance
“…The present study by Vaahersalo et al [3] adds further doubt to the field regarding the likely impact of TH in this subgroup. How could TH have a neutral effect on prognosis in these patients with non-shockable CA?…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…The present study by Vaahersalo et al [3] adds further doubt to the field regarding the likely impact of TH in this subgroup. How could TH have a neutral effect on prognosis in these patients with non-shockable CA?…”
mentioning
confidence: 48%
“…those with multiple organ failure leading to early death). Finally, the two groups were small and not comparable [3]. Indeed the aetiologies of the OHCA were different, and the prolonged median time to ROSC in the 70 patients treated with TH (25 min) was significantly higher than in patients without TH.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Hemodialysis and male gender were associated with cooling success. Vaahersalo et al [54] evaluated postresuscitation care, implementation of TH, and outcomes of ICU-treated OOHCA patients admitted to 21 ICUs. Among 548 patients included in the study, 311 had a shockable rhythm and 237 had a non-shockable rhythm.…”
Section: Cardiac Arrestmentioning
confidence: 99%
“…At that time, there were few data on the use of TH in comatose patients following cardiac arrest from other rhythms or after in-hospital cardiac arrest (IHCA), but the ILCOR advisory statement indicated that TH might also be beneficial under such circumstances. Since then, several observational studies with historical or concurrent control groups have shown benefit after cooling in comatose survivors after OHCA from non-shockable rhythms [14], although such studies carry risk of bias, and some observational studies have shown no benefit for TH after cardiac arrest from nonshockable rhythms [15]. Contrary to the prevailing opinion several years ago, mild hypothermia may also be beneficial in the presence of cardiogenic shock: in a case series of 14 such patients, cooling improved cardiac index, stroke volume and mean arterial blood pressure [16].…”
mentioning
confidence: 99%